PENGARUH PENGENDALIAN INTERNAL DAN SUMBER DAYA MANUSIA TERHADAP RISIKO KREDIT - Safitri, Aprilia; Halpiah, Halpiah; Putra, Hery Astika (Nusantara Hasana Journal, 2024)
This research aims to test and determine the influence of internal control variables and human resources on credit risk at FIF Mataram Branch. This research is quantitative research with an associative approach. The respondents in this study were 30 people. Research analysis uses multiple regression analysis and classic assumption tests consisting of normality tests, multicollinearity tests and simultaneous tests. Based on the results of the tests carried out, it was concluded that partially the human resource variable has a significant influence on credit risk. Meanwhile, the results of the simultaneous test concluded that internal control variables and human resources had a significant effect on credit risk.